Aspectos morfológicos e funcionais do corpo lúteo bovino durante a luteólise parcial e total - Trevisol, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
We aimed describe the CL characteristics during partial luteolysis, in different days of estrous cycle, after cloprostenol sodium low-dose challenge. Therefore, two projects were conduct and describe in two articles. In the first article, 32 cows were submitted to ovulation synchronization (Ovsunch +P4), 28 cows ovulated between 24 and 32 hours (h) after last GnRH (Day 0) of ovulation synchronization protocol, and were used in the project. At D6, cows were randomly divided in three treatments (moment 0): Control (2 mL of saline 0.9%; IM, n=10), 2XPGF (two doses of 500 μg of cloprostenol sodium with 2 hours interval, n=8) and 1/6PGF (83.33 μg of cloprostenol sodium, IM, n=10). Blood samples and luteal volume were collect before treatments and every 8 h, during 48 h of observations. We also collect two CL biopsies at 24 and 40 h post-treatments. The data was considered statically different when P < 0.05. Animals from 2XPGF had progesterone concentration (P4) decreased 16 h after treatment and it remain low until 48 h after treatment. In 1/6PGF, we observe a partial luteolysis, with decrease on circulating P4 and luteal volume 16 h, after that, we observe an increase in the next moments. The COX-2 and PGDH staining were more intense at 24 and 40 h, however the staining for StAR was intense only on 40 h moment. Still in 1/6PGF treatment, the luteal volume also decrease after 24 h and this moment was characterized by large luteal cells (LLC) minor area than Control, also some positive cell for FAS and FAS-L staining. In the next moments, luteal volume increase as well as cell area tend increase. In the second article, 39 cows were submitted to ovulation protocol (last GnRH = D0), 34 ovulated between 24 and 32 h after GnRH of protocol. The cows were synchronized in a way that data collect were at the same day. Each estrous cycle day were submitted in the same 3 treatments described in Article I: D7 (n=5/2XPGF, n=5/1/6PGF e n=6/control) and ...

O objetivo desse estudo foi descrever as características do corpo lúteo (CL) durante a luteólise parcial, em diferentes dias do ciclo estral, após desafio com sub-dose de cloprostenol sódico. Para tanto foram realizados dois experimentos que foram descritos em dois artigos. No artigo I, 32 vacas foram submetidas à sincronização da ovulação (Ovsynch + P4), sendo dessas, 28 ovularam entre 24 e 32 horas (h) após último GnRH (Dia 0) do protocolo. No D6 as vacas foram divididas aleatoriamente em três tratamentos (momento 0h): Controle (2 mL, salina, i.m.; n=10), 2XPGF (duas doses de 500 μg de cloprostenol sódico com 2 horas de intervalo, i.m.; n=8) ou 1/6PGF (83,3 μg de clorprostenol sódico, i.m.; n=10). Amostras de sangue e volume luteal, foram coletadas antes dos tratamentos e a cada 8 h durante às 48 h de observações. Também foram coletadas duas biopsias de CL nos momentos 24 e 40 h pós-tratamento. Valores com P < 0,05 foram considerados diferentes estatisticamente. Nos animais do tratamento 2XPGF, a diminuição da concentração plasmática de progesterona (P4) foi observada a partir de 16 h permaneceu diminuindo até 48 h pós-tratamento. No tratamento 1/6PGF foi observada a luteólise parcial, caracterizada pelas menores concentrações da P4 no momento 16 h seguido do aumento de nos momentos seguintes. As marcações de COX-2 e PGDH foram intensas nos momentos 24 e 40 h, porem a marcação para StAR foi intensa somente no momento 40 h. Ainda no tratamento 1/6PGF o volume luteal também diminuiu com 24 h e esse momento foi caracterizado pela menor área das células luteais grandes (LLC), comparada com o Controle, também algumas células positivas para a marcação de FAS e FAS-L. Nos momentos seguintes o volume luteal aumentou assim como a área das células tiveram tendência em aumentar. No artigo II, 39 vacas foram divididas em dois grupos e submetidas a sincronização da ovulação (Ovsynch + P4), sendo dessas ...
Functional and morphological changes in bovine corpus luteum during full and parcial luteolysis and luteal feature to low dose of cloroprostenol sodium during estrous cycle
Keywords: Corpo lúteo; Progesterona; Prostaglandinas; Luteólise; Ciclo estral; Estrous Cycle